Responses to Fatwas of Islamic Religious Leaders and Institutions during the Coronavirus Disease (COVID-19) in the Philippines: Looking at How Guidance Was Provided to Muslim Communities in the Philippines. - et. al., Sheryl R. Morales, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Philippine constitution guarantees the free exercise of religion and religious worship. The law forbids public officials from interrupting religious activities. However, with the sharp rise of Coronavirus (COVID-2019) infection all over the world, the Inter-Agency Task Force (AITF) on Emerging Infections Disease created resolutions to assess, monitor, contain and prevent the spread of the pandemic. Religious leaders and Islamic institutions are no exceptions and they must abide to these resolutions including mass gatherings, safety procedures on burials, and strict observance of social distancing. Muslims strictly perform five times a day prayer, Friday Jamaah prayer, and bury the dead in accordance to Islamic practices mentioned in the Quran. Therefore, the study focus on how Islamic leaders and institutions responded to AITF resolutions to prevent the spread of the pandemic. The data were collected from mixed sources: from official announcements, social media accounts, and by phone interviews. Meaningful central themes were derived from the data. Findings noted responses of Muslim communities focused on (1) suspension of collective religious activities and programs until the pandemic is over; (2) abide by government directives on how to be safe from the threat of COVID-19; (3) institutionalization of positive sanitation practices of their facilities personnel and families; (4) cancellation of classes and their religious learning institutions; and (5) public interest and dharurah (possibility of harm or injury). In conclusion, the concept of collective duty (farḍ kifāya) as a basic of principle of Islam was practiced by Islamic religious leaders and institutions. Hence, maintaining social